Pre-validation of a reporter gene assay for oxidative stress for the rapid screening of nanobiomaterials - Martin, Sebastin; de Haan, Laura; Miro Estruch, Ignacio; Eder, Kai Moritz; Marzi, Anne; Schnekenburger, Jürgen; Blosi, Magda; Costa, Anna; Antonello, Giulia; Bergamaschi, Enrico; Riganti, Chiara; Beal, David; et al. (Frontiers in Toxicology, 2022)
Engineered nanomaterials have been found to induce oxidative stress. Cellular oxidative stress, in turn, can result in the induction of antioxidant and detoxification enzymes which are controlled by the nuclear erythroid 2-related factor 2 (NRF2) transcription factor. Here we used an NRF2 specific chemically activated luciferase expression (CALUX) reporter gene assay derived from the human U2OS osteosarcoma cell line to screen for the induction of the NRF2 mediated gene expression following exposure to biomedically relevant nanobiomaterials. Specifically, we investigated Fe3O4-PEG-PLGA nanoparticles while Ag (NM300K) and TiO2 (NM101) nanoparticles from the Joint Research Center were used as reference or benchmark materials. The viability of the cells was determined by using the Alamar blue assay. We performed an interlaboratory study involving seven different laboratories to assess the applicability of the NRF2 reporter gene assay for the screening of nanobiomaterials. The latter work was preceded by online tutorials to ensure that the procedures were harmonized across the different participating laboratories. Fe3O4-PEG-PLGA nanoparticles were found to induce very limited NRF2 mediated gene expression, whereas exposure to Ag nanoparticles induced NRF2 mediated gene expression. TiO2 nanoparticles did not induce NRF2 mediated gene expression. The variability in the results obtained by the participating laboratories was small with mean intra-laboratory standard deviation of 0.16 and mean inter laboratory standard deviation of 0.28 across all NRF2 reporter gene assay results. We conclude that the NRF2 reporter gene assay is a suitable assay for the screening of nanobiomaterial-induced oxidative stress responses.